EFFECTIVENESS ENHANCED RECOVERY AFTER CAESAREAN SURGERY (ERACS) ON CONSCIOUS RECOVERY TIME IN SECTIO CAESAREA PATIENTS IN THE RECOVERY ROOM OF RSAD TK. II UDAYANA - Yustina Ni Putu Yusniawati; Emanuel Ileatan Lewar; I Gade Agus Shuarsedana Putra; I Gusti Ayu Nandita Arta Putri (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Enhanced recovery after Caesarean surgery (ERACS) is a method of perioperative care in the form of a multimodal approach. ERACS is a good method of pain management by reducing opioid use by 30-50 percent and using intravenous fluid therapy and a good combination of anti-nausea drugs. The ERACS technique was carried out starting from pre-intra and post-surgery. In its implementation, ERACS has various benefits, namely reducing postoperative complications, accelerating conscious recovery, saving costs and reducing morbidity. Urgency of this research is to find out effective surgical methods to speed up early postpartum mobilization without pain. Objective: To determine the effectiveness of the ERACS technique for conscious recovery in sectio caesarea patients with spinal anesthesia in the recovery room. Method: This study used a quasi-experimental with a cross-sectional approach using 2 groups, namely the control group and the treatment group. This research was carried out in June-August 2022 at TK II Udayana Hospital with 60 respondents for the control group and 60 for the treatment group. The research instrument uses a standard bromage score observation sheet. The research process was carried out by giving informed consent to the 2 groups and then post-surgery an assessment of conscious recovery was carried out in both groups. Results: The results of the study in the treatment group showed that the ERACS method had a faster recovery time of 15-30 minutes. The control group, namely the conventional method, has a longer conscious recovery time of 30-60 minutes. The statistical test Mann-Whitney test is sig <0.05 that can be concluded that ERACS is effective in decreasing the time to recover consciousness in the recovery room in patients with elective sectio caesarea surgery at RSAD Tk.II Udayana. Conclusion: The ERACS method is effective in accelerating the time to recover from consciousness in the recovery room and accelerating recovery in patients with elective sectio caesarea surgery at RSAD Tk.II Udayana. Therefore, the application of ERACS can be an effective choice to accelerate postoperative recovery with caesarean section.